2020
DOI: 10.1101/2020.03.02.973479
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Sociality enhances survival in science, especially for female researchers

Abstract: Intense competition for limited opportunities means the career path of a scientist is a challenging one, and female scientists in particular are less likely to survive in academia. Collaboration is a key factor in scientific advances, and in social species enhanced sociality improves fitness and longevity. Yet whether sociality influences career progression and survival in science, and how this might differ between genders, is largely unknown. We built authorship social networks from publication records to tes… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 133 publications
(141 reference statements)
0
1
0
Order By: Relevance
“…Monnapula-Mapesela (2017) and Madileng (2014) also found that Black women academics needed the perseverance to progress to higher levels. According to Nkumane (2018) and Van der Wal et al (2020), Black women academic researchers should be encouraged to collaborate with other academics to improve their research skills. Boateng (2018) is in agreement that collaboration might be useful for emerging Black women academics to progress in their careers (Boateng 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Monnapula-Mapesela (2017) and Madileng (2014) also found that Black women academics needed the perseverance to progress to higher levels. According to Nkumane (2018) and Van der Wal et al (2020), Black women academic researchers should be encouraged to collaborate with other academics to improve their research skills. Boateng (2018) is in agreement that collaboration might be useful for emerging Black women academics to progress in their careers (Boateng 2018).…”
Section: Discussionmentioning
confidence: 99%